Analisis Efektivitas Etf Syariah sebagai Instrumen Investasi Halal di Pasar Modal Indonesia - Ema Nur Syahfitri; M. Yasfin Nasution; Annisa Khoiri; Miranda Panjaitan; Willia Wahyuni; Ikram Muharril; Sunan Agung Nugroho; Nur Aisyah Tanjung; Muhammad Ikhsan Harahap (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2026)
This study aims to analyze the effectiveness of Sharia Exchange Traded Funds (ETFs) as halal and efficient investment instruments in the Indonesian Capital Market, by comparing their financial performance, operational efficiency, and sharia compliance with benchmark indices and active sharia investment products. The method used is quantitative descriptive with purposive sampling on three active Sharia ETFs on the Indonesia Stock Exchange (IDX) during the period 2022–2024, using daily price data, NAV, and operational costs to calculate the Average Annual Growth Rate (AAGR), Sharpe Ratio, Total Expense Ratio (TER), and Tracking Error (TE) values. The results show that Sharia ETFs are highly effective, evidenced by low TE (below 0.80%) confirming the accuracy of index replication, significantly lower TER (average 0.85% vs. 2.0-3.5% in active mutual funds) that provides competitive net returns, and superior Sharpe Ratio, confirming that Sharia ETFs are a low-cost and liquid diversification solution that is fully sharia-compliant.